Exploration of Heavy Metal Tolerant Bacteria From Rhizosphere Soil of Tana Toraja's Bamboo - Widiastini Arifuddin (Jurnal Inovasi Pendidikan dan Sains, 2022)
Tana Toraja has a high diversity of bamboo. Bamboo plants play a significant role in bioenergy programs and environmental management. Some studies had showed bamboo as a phytoremediation agent for heavy soil contaminated soil. Their rizosphere soil also an ideal habitat for potential microorganisms, which has been reported by many studies. In this study we used five bacteria isolates, which isolated from different rhizosphere soil of tana torajas’ bamboo, namely Htl.2, Hpr.6, Hk.1, Hh.5 and Hb.1. We used three different heavy metal, they are mercury (Hg), plumblum (Pb) and chromium (Cr) with a consentration range are 5 ppm and 10 ppm. The ability of isolates bacteria to adapt to heavy metals was indicated by the formation of clear zones on petridisc. Based on the results, all bacterial isolates showed different responses to heavy metal presence in their media culture. Isolates bacteria Htl2, Hpr.6 and Hb.1 form a relatively high clear zone in the heavy metal mercury (Hg). Isolates bacteria Hh.5, Hpr.6 and Hk.1 showed a high clear zone for plumbum metal (Pb), while in chromium metal (Cr) media there are an Hb.1, Hh.5 and Hpr.6 isolate forms a high clear zone. Based on morphological observations, there are four bacteria isolates classified as Gram-negative, and one isolate as Gram-positive. These results are preliminary studies to find bacteria that are prospectively used in the rehabilitation of heavy metal contaminated soils.